Public Policy from A State Administration Perspective Mandalawangi Bumdes Development Strategy Tasikmalaya District - Astri Siti Fatimah; Deni Sudrajat; Beni Hartanto; Tine Badriatin (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
This research aims to develop a strategy for developing Village-Owned Enterprises (BUMDes) in Mandalawangi Village, Tasikmalaya Regency. Bumdes is an economic institution owned by village communities with the aim of improving the welfare of village communities. This research uses qualitative methods with data collection techniques through interviews, observation and documentation studies. The research results show that Bumdes Mandalawangi has great potential in developing various economic businesses in the village. However, to optimize this potential, the right strategy is needed. The Mandalawangi Bumdes development strategy is expected to help improve the welfare of village communities, create jobs and reduce dependence on certain economic sectors. Apart from that, this strategy can also be a guide for other villages in developing their Bumdes.